Islam by smartphone: reading the Uyghur Islamic revival on WeChat. Issue 1 (2nd January 2019) - Harris, Rachel; Isa, Aziz
ABSTRACT: The official Chinese view of the Uyghur Islamic revival is overwhelmingly dominant. Because of the extraordinary measures taken to shield from international view the actual developments in the region and to silence Uyghur voices, we lack a clear sense of what it is to be a Muslim in contemporary Xinjiang. This article explores debates within Uyghur society about faith, politics and identity as they are revealed through the social media platform WeChat. It aims to disrupt the dominant narratives and enable new understandings of the changing patterns of religiosity and violence in the region. It focuses on the use of social media to access affective experiences of religion, projects of self-fashioning, and the new geographies of knowledge and experience formed as Uyghurs turned to the readily available scripts circulating in the wider Islamic world and adapted them to a very local sense of crisis.